The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1002/pola.24970
|View full text |Cite
|
Sign up to set email alerts
|

Formation of triblock copolymers via a tandem enhanced spin capturing—nitroxide‐mediated polymerization reaction sequence

Abstract: The preparation of ABA‐type block copolymers via tandem enhanced spin capturing polymerization (ESCP) and nitroxide‐mediated polymerization (NMP) processes is explored in‐depth. Midchain alkoxyamine functional polystyrenes (Mn = 6200, 12,500 and 19,900 g mol−1) were chain extended with styrene as well as tert‐butyl acrylate at elevated temperature NMP conditions (T = 110 °C) generating a tandem ESCP‐NMP sequence. Although the chain extensions and thus the block copolymer formation processes function well (yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 41 publications
(58 reference statements)
0
10
0
Order By: Relevance
“…They concluded that while the then available data did not allow model discrimination between the schemes, the apparent incompatibility of the models, while significant, was less than suggested in some papers. They, [26] and more recently, Junkers [27] have pointed out the need for more reliable measurements of kinetic parameters to fully resolve the situation.…”
Section: Mechanisms For Retardationmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that while the then available data did not allow model discrimination between the schemes, the apparent incompatibility of the models, while significant, was less than suggested in some papers. They, [26] and more recently, Junkers [27] have pointed out the need for more reliable measurements of kinetic parameters to fully resolve the situation.…”
Section: Mechanisms For Retardationmentioning
confidence: 99%
“…include those on the kinetics and mechanism of RAFT polymerization, [26,27] RAFT agent design and synthesis, [28] the use of RAFT to probe the kinetics of radical polymerization, [29] microwaveassisted RAFT polymerization, [30,31] RAFT polymerization in microemulsion, [32] end-group removal/transformation, [33][34][35][36] the use of RAFT in organic synthesis, [37] the combined use of RAFT polymerization and click chemistry, [38] the synthesis of star polymers and other complex architectures, [39][40][41][42] the synergistic use of RAFT polymerization and ATRP, [43,44] the synthesis of self assembling and/or stimuli-responsive polymers, [45][46][47] and the use of RAFT-synthesized polymers in green chemistry, [48] polymer nanocomposites, [49][50][51] drug delivery and bioapplications, [41,46,47,[52][53][54][55][56][57][58][59][60] and applications in cosmetics [61] and optoelectronics. [62] The process is also given substantial coverage in most recent reviews that, in part, relate to polymer synthesis, living or controlled polymerization or novel architectures.…”
Section: Introductionmentioning
confidence: 99%
“…At 80 °C, the midchain alkoxyamine of PS cannot efficiently dissociate and polymerization of ethylene is not occurring. 32 When polymerizations are carried out at higher temperatures (100 and 120 °C) the MWDs are successfully shifted toward higher MW, leaving no initial PS material behind as can be seen from the monomodality of the product distribution. Formation of homopolymer (also due to the lack of addition of any conventional initiator) can thus be excluded, and ABA triblock copolymers are exclusively obtained from the chain extension.…”
Section: Scheme 1 Full Mechanism Of Escp In Ethylene Polymerizationmentioning
confidence: 99%
“…The reader interested in this technique should refer to the literature . ESCP has been employed for controlling the polymerization of S, n BA, ethylene, and NIPAAm in either organic or aqueous solutions and via thermally or photo‐chemically initiated systems …”
Section: Nmp Of Mma: Why Does It Fail?mentioning
confidence: 99%